Detection of basal stem rot disease by stem tissue identification - Farizul Hafiz, Kasim; Mohamed Zulkali, Mohamed Daud; Norahim, Ibrahim; Suhardy, Daud; Saiful Azhar, Saad; Marni Azira, Markom (Nanyang Technological University, 2008)
Organized by Nanyang Technological University, 3rd - 5th December 2006 at Nanyang Technological University, Singapore.